Unveiling Engagement in Asynchronous Writing: A Comprehensive Exploration of Approaches and Indicators – A Systematic Literature Review - Nur Arifah Drajati; Dewi Rochsantiningsih; Martono Martono; Dewi Cahyaningrum; Elisa Indriyani PH; Agustina Tyarakanita (AL-ISHLAH: Jurnal Pendidikan, 2024)
In developing the learners’ language competence, many educational institutions altered teachers to integrate computer-mediated communication (CMC) synchronously and asynchronously. However, the issue of engagement becomes another issue to be handled. Accordingly, in this literature review of 20 qualitative, 7 quantitative, and 8 mixed-method studies published in the high-ranked database from 2000-2021, we aim to examine the approaches to evaluate and indicators to facilitate the learners’ engagement, specifically on writing asynchronously. Asynchronous CMC became the concern of this study as it supports the learners to follow the simultaneous discussion and supports multiple learning styles. The reviewed studies were identified using behavior, cognition, and emotion approaches to evaluate the learners’ engagement. Thus, the types of indicators to facilitate the learners’ engagement are input, process, and outcomes. Finally, this review suggests it is useful to design writing courses that effectively conceptualize evaluation approaches and indicators to facilitate the learners’ engagement.